Concepts of Agri-Competitiveness in Theorical and Imperical Researchs - Bui Van Dung; Van Hoang Thi Thuy; Anh Ho Thi Dieu; Le Ho Thi Thuy (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2020)
The purpose of this study is to analyze the competitiveness of exported agricultural products through theoretical and empirical studies, estimation methods and determinants. Not only summarizing the competitiveness theories of agricultural products exported from previous studies, the article also clarifies the concept of competitiveness of agricultural products at the level of products/services, firms/ farms, industry, thereby helping firms from agricultural countries - which rely heavily on agricultural production and agricultural products export to find the right ways to identify definitions and concepts, then choose the right methods of measurement, compare its export agricultural products competitiveness. Since, the study also proposed the use of synthetic indicators to measure the competitiveness of agricultural exports which is an important basis for the state agencies in the study and propose their export policy of agricultural products in the near future.